Relationship Stability Through Lenses of Complexity. - Karakurt, Gunnur (American Journal of Family Therapy)
Research on relationship stability usually considers the effect of couple outcomes and individual differences on relationship stability in isolation from each other. These separate bodies of research often lead to inconsistent results. In order to better understand relationship stability and explain inconsistencies in the literature, it is important to investigate more complex models that integrate couple outcomes and behaviors with individual differences. Motivated by these considerations, we examined the complex interplay between personal characteristics, couple interactions, and relationship stability. In particular, we investigated the relationships among investment model, big five personality traits, attachment dimensions, relationship factors, and relationship stability. Participants of this study included 162 individuals (Female N = 117) who are currently in a relationship from a large Midwestern university campus. Analyses were conducted using Structural Equation Modeling. Examination of the structural path parameters indicated that attachment had significant direct effect on personality, relationship factors, and relationship stability. Personality also had a significant direct effect on relationship stability. Finally personality had no direct effect on relationship factors and relationship factors had no direct effect on relationship stability. These results suggest that the effect of personality on relationship stability is direct, rather than being mediated by relationship factors.